Preparation method and application of boron isotope separation resin microspheres
By preparing boron isotope separation resin microspheres loaded with iron tetroxide, the bed pressure drop and flow rate problems used by nanomaterials in chromatographic columns are solved, and efficient boron isotope separation and long-life chromatographic column performance are achieved. High 10B abundance conditions.
Patent Information
- Application Number
- CN202411324573.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
In the existing boron isotope separation technology, nanomaterial ultrafine powders are used in chromatographic columns with large pressure drop, low flow rate, and uneven liquid flow distribution. The elution process is complicated and the life of adsorption separation materials is short. , and is only effective under conventional aqueous boric acid solution conditions, and does not perform well under high 10B abundance conditions.
Prepare boron isotope separation resin microspheres, sulfonate and loaded with iron tetraoxide nanoparticles by crosslinking polystyrene-divinylbenzene resin microspheres, and uniformly spray them with ferric chloride-ferrous chloride aqueous solution, combined with The ammonia nitrogen flow treatment forms a macroporous structure and uniform distribution of iron tetroxide nanoparticles, improving adsorption and separation efficiency.
Highly efficient 10B enrichment in aqueous boric acid-sodium hydroxide solution of pH 6-7.5 was achieved, the service life of the chromatographic column was extended, the overall performance was better than that of the prior art, and it performed well under high 10B abundance conditions.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of boron isotope separation, and specifically relates to a preparation method and application of boron isotope separation resin microspheres. Background Art
[0002] 10 B and 11 B is the two stable isotopes of boron, with natural abundances of 19.9% and 80.1% respectively. 10 The thermal neutron capture cross section of B is much larger than 11 B, used in the nuclear industry for reactor control rod materials (such as boron carbide), pressurized water reactor coolants (such as boric acid aqueous solution) and neutron shielding materials (such as boron-containing polyethylene), and in medicine as a targeting agent for the treatment of certain tumors (boron neutron capture therapy); in these applications, 10 The abundance of B has certain requirements, except for some neutron shielding materials, it is above 85%. 10 The main methods of B are: BF3 low temperature distillation, chemical exchange distillation and chromatography; among them, chromatography has the characteristics of energy saving and safety. 10 B and 11 B, is a separation method with great development potential
[0003] In the prior art, ion exchange or adsorption resins, such as strongly acidic cation exchange resins, strongly basic anion exchange resins, weakly basic anion exchange resins, and boron-specific adsorption resins AMBERLITE IRA743 and weakly acidic cation exchange resins, are used to adsorb boric acid in aqueous solution. 10 B and 11 The adsorption and separation effects of B isotopes are poor and have no practical value ( 10 B / 11 B separation coefficient, i.e., separation factor, is lower than 1.1). Therefore, it is necessary to develop a new boron adsorption separation material for boron isotope separation in boric acid aqueous solution.
[0004] CN109205656A provides a method for preparing metal oxide nanomaterials and a method for separating boron isotopes by using the metal oxide nanomaterials as a simulated moving bed stationary phase. Nine metal oxide nanomaterials are prepared, namely Cu2O, CuO, ZnO, Al2O3, MnO2, TiO2, Cr2O3, CeO2, and ZrO2. In the embodiment, 0.10 g of the prepared metal oxide nanomaterials are weighed and added to a 0.5 mol / L boric acid aqueous solution, shaken at 200 rpm for 3 hours, filtered, centrifuged, and the boric acid concentration and isotope abundance in the aqueous solution after treatment are detected, and the boron isotope is calculated. 10 B / 11The separation coefficient of B is 1.112-1.308. The invention content part records the method of using the metal oxide nanomaterial as a simulated moving bed stationary phase to separate boron isotopes, which includes the following steps: (1) first prepare a boric acid aqueous solution, adjust the pH value of the boric acid aqueous solution to 6-12 with a sodium hydroxide aqueous solution to become a boric acid stock solution, and then filter the boric acid stock solution and an acetic acid (or hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid) aqueous solution with a pH value of 4-6 with a filter membrane, and ultrasonically degas; (2) the simulated moving bed includes zones I-IV, each zone is composed of 2-8 chromatographic columns; the metal oxide nanoparticles are used as the simulated moving bed stationary phase; the boric acid stock solution obtained in step (1) is continuously injected into the chromatographic column of the simulated moving bed, and the acid aqueous solution obtained in step (1) is used as an eluent. When the simulated moving bed reaches equilibrium, the extraction end valve is opened to collect the rich 10 B Boric acid is an aqueous solution, and the rich 11 B boric acid aqueous solution; but the embodiment part does not record the specific method and effect of separating boron isotopes by simulated moving bed stationary phase. One problem with CN109205656A is that the boric acid stock solution with a pH value of 6-12 needs to be prepared by adding a significant amount to a large amount of alkali to the boric acid aqueous solution, and the acid concentration of the eluent, that is, the acetic acid (or hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid) aqueous solution with a pH value of 4-6, is relatively low. It is speculated that the elution effect after acid-base neutralization during the operation of the simulated moving bed is relatively general.
[0005] CN109464981A provides a method for preparing a magnetic nanomaterial and a method for separating boron isotopes using the magnetic nanomaterial as a simulated moving bed stationary phase, and discloses methods for preparing four magnetic nanomaterials: Fe3O4, SiO2@Fe3O4, Carbon@Fe3O4, and Fe3O4@CuO. For example, a method for preparing a magnetic nanomaterial Fe3O4 comprises the following steps: (1) weighing 8.1 g of FeCl3·6H2O and 3.9 g of FeCl2·4H2O, placing them in a round-bottom flask, adding 540 mL of deionized water and a magnet, fixing the round-bottom flask on a magnetic stirrer, and connecting a balloon filled with nitrogen to dissolve the substances under magnetic stirring; (2) after the two substances are completely dissolved, under strong magnetic stirring and nitrogen protection, adding 60 mL of ammonia water to adjust the pH to about 8, at which point the solution changes from red to black, and the reaction time is 1 hour; (3) after the reaction is completed, separating the product with a magnet and washing it, and adjusting the pH of the solution to neutral with hydrochloric acid during the last washing; (4) drying the product under vacuum at 40°C for 8 hours. In the embodiment, 0.10 g of the prepared metal oxide nanomaterials were weighed and added to a 0.5 mol / L boric acid aqueous solution, shaken at 140 rpm for 6 hours, filtered, centrifuged, and the boric acid concentration and isotope abundance in the aqueous solution after treatment were detected to calculate the boron isotope. 10 B / 11B separation factor; the four materials all showed a relatively high boron isotope separation factor of 1.118-1.332, among which Fe3O4 had the best overall effect. The invention content part records the method of separating boron isotopes using the magnetic nanomaterials, including: first preparing a boric acid aqueous solution, adjusting the pH value of the boric acid solution to 5-9 with a sodium hydroxide aqueous solution to become a boric acid stock solution, and then filtering the boric acid stock solution and acetic acid or hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid aqueous solution with a pH value of 2-6 with a filter membrane, and ultrasonically degassing; the simulated moving bed includes zones I-IV, each zone is composed of 2-6 chromatographic columns; the magnetic nanomaterial is used as the stationary phase of the simulated moving bed; the boric acid stock solution is continuously injected into the chromatographic column of the simulated moving bed, and the acid aqueous solution is used as the eluent. When the simulated moving bed reaches equilibrium, the extraction end valve is opened to collect the rich 10 B Boric acid is an aqueous solution, and the rich 11 B is an aqueous solution of boric acid; however, the specific method and effect of separating boron isotopes by simulating a moving bed stationary phase are not described in the examples.
[0006] The above-mentioned prior art has defects in writing and disclosure, but boron isotopes 10 B / 11 The determination method of B separation factor, material preparation method and separation factor results are provided. 10 B / 11 The doctoral dissertation "Application and Mechanism Study of Boron Adsorption and Boron Isotope Separation by Magnetic Nanoparticles (Fe3O4)" (Chen Tao, Tianjin University, May 2022) discloses the effects of Fe3O4 nanoparticles (prepared by co-precipitation method) on the adsorption, desorption and isotope separation of boron in aqueous boric acid solutions of different concentrations, pH values and temperatures, as well as the performance attenuation of the material, which has a higher reference value than CN109464981A.
[0007] The above-mentioned prior art has three technical problems: first, the prepared nano material is an ultrafine powder. When used as a chromatographic column stationary phase and continuously separated by the boric acid aqueous solution, there are problems such as large bed pressure drop, low flow rate and processing capacity, and liquid flow distribution being greatly affected by the uneven particle size distribution. Although this problem can be solved to a certain extent by pressure molding, crushing, and screening the nano powder to obtain granules with a particle size of 0.2-1 mm, and then filling them into the chromatographic column, the actual effect is not good, mainly because there is a contradiction between strength and internal pore volume. When the strength is guaranteed, the internal pores are significantly compressed, and the adsorption and separation ability of the granules for boric acid is greatly reduced; second, the elution process requires two liquid flows of the dilute acid and water, and the dilute acid corrodes the adsorption and separation material, making the chromatographic separation operation more complicated and the life of the adsorption and separation material more difficult to guarantee; third, only the conventional boric acid aqueous solution, i.e., 10B and 11 The results of boron adsorption, desorption and isotope separation under the conditions of B abundance of 19.9% and 80.1% are not provided. 10 B shows the effect under conditions of high abundance boric acid aqueous solution.
[0008] In the master's thesis "Preparation of Fe3O4-loaded Resin and Study on Boron Isotope Separation Performance" (Wang Qingfeng, Tianjin University, May 2021), a microsphere material (Fe3O4@Resin) prepared by pre-exchange-coprecipitation method and loaded with Fe3O4 nanoparticles (loading amount of about 8.1wt%) by macroporous strongly acidic cation exchange resin (D001 resin microsphere) was disclosed, and its physical and chemical properties and chromatographic separation of boron isotopes were studied; the indicators of the D001 resin used were: styrene-divinylbenzene system, the functional group was -SO3 - , mass total exchange capacity (dry) ≥ 4mmol / g, volume total exchange capacity (wet) ≥ 1mmol / mL, particle size 0.315-1.25mm, water content 42-55%. Among them, Fe3O4@Resin-1 has a better effect. The preparation method is as follows: 40mL D001 resin converted to hydrogen form after pretreatment, 8.1g FeCl3·6H2O and 540mL deionized water are added to a round-bottom flask, and stirred for 12h under N2 conditions to make D001 resin and Fe 3+ Perform sufficient ion exchange; then add 3.9g FeCl2·4H2O and wait until it is completely dissolved in the mixture (Fe 3+ with Fe 2+The reaction was completed after 1 hour, and Fe3O4@Resin-1 particles (the iron oxide content was 8.1 wt % based on the dry basis of Fe3O4@Resin-1 and Fe3O4) were obtained by static precipitation. The particles were washed 3 times with ethanol and deionized water respectively, dried in vacuum at 40°C for 10 hours, and sieved with 24-mesh and 32-mesh sieves to obtain particles with a particle size of 0.56-0.8 mm, which were then used in subsequent experiments. Fe3O4 nanoparticles (without resin) were also synthesized by coprecipitation method as a control: 8.1gFeCl3·6H2O, 3.9gFeCl2·4H2O and 540mL deionized water were added to a round-bottom flask, stirred under N2 conditions, and 60mL ammonia water was added to cause coprecipitation reaction after all dissolved. The remaining operation steps and conditions were consistent with those of Fe3O4@Resin-1, and finally a microsphere material loaded with Fe3O4 nanoparticles was obtained. The XRD method detected that the grain size of the Fe3O4 nanoparticles on the surface of Fe3O4@Resin-1 was 13nm, and the grain size of the pure Fe3O4 nanoparticles (without resin) in the control was also 13nm; the SEM method detected that the surface of the Fe3O4@Resin particles was coated with a layer of Fe3O4 nanoparticles, and it was relatively rough. The zero charge point (pHzpc) of Fe3O4@Resin-1 is 6.75. The boron adsorption and separation factor are both large when the pH of the boric acid aqueous solution is 6-7. The maximum boron adsorption is 2.869 mg·g at pH 7. -1 , at pH 6, about 2.65 mg g -1 , which significantly decreased at other pH values; the separation factor was 1.315 at pH 6 and about 1.305 at pH 7, which decreased at other pH values; the adsorption kinetics data were consistent with the pseudo-second-order kinetic model; the adsorption isotherm data were consistent with the Langmuir model. The activated Fe3O4@Resin-1 material (58.81 g) was wet-filled into a stainless steel column with a length of 25 cm and an inner diameter of 2.2 cm, and boron isotope chromatographic separation (dynamic separation) was performed: the boron concentration was 5.405 g·L -1 , 10 B abundance 19.78% ( 11 The boric acid aqueous solution (B abundance 80.22%) was adjusted to pH 7 with sodium hydroxide aqueous solution and the flow rate was 5 mL min -1 , the column temperature was 25℃, and the liquid was continuously injected for 60 min; then the concentration of 0.01 mol·L -1 The hydrochloric acid solution was used as the eluent at a flow rate of 5 mL min -1, the column temperature was 25℃, and the liquid was continuously added for 1.5h to elute the boric acid adsorbed on the Fe3O4@Resin-1 filler; finally, deionized water was continuously added until the effluent was neutral, and the hydrochloric acid solution in the chromatographic column was completely replaced by water to complete the regeneration; the adsorption-regeneration process was repeated five times. As a result, the separation factor reached 1.312, the column pressure drop was below 2MPa, and the elution was 10 The boric acid aqueous solution with a boric acid abundance of 22.76% was used; however, the boron adsorption separation performance gradually decreased with each adsorption-regeneration process. 10 The adsorption amounts of B are 0.03275g, 0.03218g, 0.03172g, 0.03131g, and 0.03088g, respectively, and the recovery rates are 95.98%, 94.31%, 92.97%, 91.76%, and 90.50%, respectively. This prior art still has three problems: First, Fe 3+ with Fe 2+ The molar ratio of the feed is 3:2, and the 3+ with Fe 2+ The molar ratio of the feed required to generate Fe3O4 by neutralization precipitation reaction is different from 2:1, which indicates that part of Fe is needed in the preparation process. 2+ Oxidation of the prepared microsphere material may result in the oxidation of the prepared microsphere material in the advanced boric acid-sodium hydroxide aqueous solution (pH 7, boron concentration 5.405 g·L -1 ), using hydrochloric acid solution (0.01 mol·L -1 ) desorption, and then washing with deionized water to neutrality, the adsorption and separation performance inevitably changes, and the Fe3O4 nanoparticles loaded on the microsphere material are basically coated on the surface of the resin microspheres. Under the action of the extrusion force of the chromatographic column bed, the Fe3O4 nanoparticle coating is easily worn and falls off; secondly, the elution process still requires the two liquid flows of dilute acid and water, and the dilute acid corrodes the adsorption and separation material, making the chromatographic separation operation more complicated and the life of the adsorption and separation material more difficult to guarantee; thirdly, it only provides a conventional boric acid aqueous solution, that is, 10 B and 11 The results of boron adsorption, desorption and isotope separation under the conditions of B abundance of about 20% and about 80% are not provided. 10 B shows the effect under conditions of high abundance boric acid aqueous solution.
[0009] Therefore, it is necessary to prepare microspherical materials with better overall performance and capable of being loaded into chromatographic columns for boron isotope separation. 10 B is enriched to a higher degree and the column has a longer service life. Summary of the invention
[0010] In order to solve the above technical problems, the present invention provides a preparation method of boron isotope separation resin microspheres and application thereof.
[0011] The method for preparing boron isotope separation resin microspheres of the present invention comprises the following steps:
[0012] (1) Cross-linking degree 15-30, specific surface area 100-180m 2 / g, pore volume 0.6-1.0mL / g, dried (120℃x3h baking loss ≤0.2wt%) polystyrene-divinylbenzene resin microspheres, adding dimethyl sulfoxide in air-tight and anhydrous conditions, heating to 50-65℃ for swelling for more than 3h, adding 93-98wt% concentrated sulfuric acid for sulfonation treatment during stirring, controlling the temperature to 55-65℃, and performing solid-liquid separation after the sulfonation rate reaches 0.3-0.4mmol / g, washing the microspheres with water until the pH value is ≥2, adding 2-5mol / L ammonia solution for immersion for 2-5h for primary ion exchange transformation from hydrogen type to ammonium type, washing with water to obtain water-containing ammonium type macroporous polystyrene-divinylbenzene ion exchange resin microspheres;
[0013] During the sulfonation treatment, the weight ratio of polystyrene-divinylbenzene microspheres, dimethyl sulfoxide, and concentrated sulfuric acid is 1:(4-5):(0.3-0.5);
[0014] (2) The ammonium-type macroporous polystyrene-divinylbenzene ion exchange resin microspheres containing water in step (1) are transferred to a rotary drum that can be evacuated, equipped with external heating and an atomizing nozzle, sealed and started to rotate, and vacuum dried at 60-70° C. until the water content is less than 1wt% to obtain dried ammonium-type resin microspheres; further evacuated and cooled to 50-60° C., filled with high-purity nitrogen to positive pressure, and atomized sprayed with a ferric chloride-ferrous chloride aqueous solution with a concentration of 2-3 mol / L and a temperature of 50-60° C. for 4-6 hours, and the drum is continuously rotated for 0.5-1 hour until the resin microspheres After all the surface solution is absorbed, the rotation is stopped, and the mixture is allowed to stand for 3-5 hours for homogenization (homogenization of the ferric chloride-ferrous chloride aqueous solution initially absorbed in the resin microspheres) and secondary ion exchange transformation from ammonium type to iron type, and the temperature of the resin microsphere material is maintained at 50-60° C. and the positive pressure in the drum is maintained during the spraying and homogenization and secondary ion exchange transformation process; the spraying volume of the ferric chloride-ferrous chloride aqueous solution is 70-85% of the saturated water absorption volume of the dried ammonium type resin microspheres; in the ferric chloride-ferrous chloride aqueous solution, the molar ratio of ferric chloride to ferrous chloride is 2:1;
[0015] The drum is started, and the external heating temperature is controlled to be 60-70° C. and the required vacuum conditions are controlled. Within 8-12 hours, 25-40% of the total weight of the water contained in the resin microsphere material is uniformly evaporated and removed, and high-purity nitrogen is filled to positive pressure, and the temperature of the resin microsphere material is reduced to 50-60° C.; the drum continues to rotate, and a nitrogen gas flow with a temperature of 50-60° C., a relative humidity of 35-45%, and 0.5-1v% ammonia is introduced at a required fixed flow rate to treat the resin microsphere material, so that no ammonia is consumed during ventilation for 4-8 hours (that is, the ammonia content in the outlet and inlet gas flows is the same, and the three ion exchange transformation from trivalent iron type to ammonium type is carried out at the same time), and the ammonia-nitrogen gas flow is continued for 0.5-1 hour; during the treatment with the ammonia-nitrogen gas flow, the temperature of the resin microsphere material is maintained at 50-60° C. and the positive pressure in the drum is maintained;
[0016] The drum continues to rotate and high-purity nitrogen is passed through to maintain the positive pressure in the drum. Deoxygenated water at 40-50°C is sprayed on the resin microsphere material. The amount of water sprayed is 2-3 times the accumulated volume of the resin microsphere material. The drum is rotated for 30-60 minutes to wash the resin microsphere material once. The drum is stopped to discharge the liquid between the resin microspheres. The washing and drainage process is repeated 2-3 times. The drum is stopped to discharge the liquid between the resin microspheres. The drum is started to spray the resin microsphere material with a concentration of 0.8-1 mol / L and a temperature of 30-40 ℃ sodium hydroxide aqueous solution, the spraying amount is 1-1.5 times of the accumulated volume of the resin microsphere material, the drum is stopped, and the mixture is allowed to stand for 2-3 hours for four ion exchange transformation treatments from ammonium type to sodium type, and then the liquid between the resin microspheres is discharged; room temperature deoxygenated water is used instead, and the water washing and liquid discharge process is repeated 3-5 times, and then the resin microsphere material is sprayed with room temperature deoxygenated water to immerse the resin microsphere material, and the resin microsphere and the immersion water are discharged into a container pre-substituted with nitrogen and the container is sealed to obtain boron isotope separation resin microspheres.
[0017] In step (1), the polystyrene-divinylbenzene microspheres are white balls obtained by removing the porogen from the mixed ingredients containing the porogen after forming the spheres by suspension polymerization, washing with water (using hot water and cold water in sequence), and drying, with an outer diameter of 0.3-1.3 mm; the pore volume is a calculated result obtained from the measurement results of the apparent density and the skeleton density. The specific surface area is measured by low-temperature nitrogen adsorption method, and the pore volume and pore diameter are measured by scanning porosimetry.
[0018] In step (2), the atomizing nozzle adopts hydraulic atomization when spraying liquid and water, and high-purity nitrogen and ammonia-containing nitrogen gas flow are also introduced through this nozzle; the O2 content in the high-purity nitrogen is preferably less than 30ppmv, that is, less than one ten-thousandth of the volume, to avoid oxidation of ferrous chloride; the positive pressure maintained by nitrogen filling the drum can be 15-30kPa to control the infiltration of O2 in the air; during the vacuum drying of the ammonium type resin microsphere material, the air in the gap between the resin microspheres and the drum is basically removed as the steam is extracted; the nitrogen gas flow with a temperature of 50-60°C, a relative humidity of 35-45%, and ammonia content of 0.5-1v%, preferably has an O2 content of less than 30ppmv, and its relative humidity is controlled by a condensation method or a desiccant method The process of uniformly evaporating and removing 25-40% of the total weight of water contained in the resin microsphere material (loaded with ferric chloride-ferrous chloride aqueous solution) at 60-70° C. and vacuum conditions can be achieved by adjusting the vacuum degree by fixing the external heating temperature, and controlling the condensation amount of the exhaust steam to be basically uniform; the deoxygenated water is pure water obtained by removing impurities such as O2 and CO2 from deionized pure water or reverse osmosis pure water through slight boiling, and the sodium hydroxide aqueous solution is prepared with deoxygenated water; the washing end point of the boron isotope separation resin microspheres can be determined according to the conductivity of the exhaust water, and the conductivity of the exhaust water can be lower than 10μs / cm, preferably lower than 5μs / cm.
[0019] In step (2), the ferric chloride-ferrous chloride aqueous solution may also contain 0.01-0.03 mol / L titanium trichloride, which is found to improve the boric acid adsorption capacity of the prepared boron isotope separation resin microspheres and 10 B. 11 B separation effect.
[0020] The boron isotope separation resin microspheres prepared by the method of the present invention are suitable for use in a boric acid-sodium hydroxide aqueous solution at pH 6-7.5. 10 B and 11 The effective method for separating B is chromatography; the specific operating conditions include: the column temperature is 15-35℃, the boric acid concentration in the boric acid-sodium hydroxide aqueous solution is 80-95% of the saturated concentration in water under the column temperature condition, the desorption liquid is pure water, and the apparent or axial flow rate of the boric acid-sodium hydroxide aqueous solution or pure water in the bed is 0.4-0.6m / h, which has a high 10 B. 11B adsorption and separation efficiency. Since the boron isotope separation resin microspheres are easy to settle in the boric acid-sodium hydroxide aqueous solution and pure water, the liquid is fed in from the top and out from the bottom; a separation bed filled with the resin microspheres is arranged in the cylinder of the chromatographic column, a compression screen is arranged above the separation bed to prevent the flow of the resin microspheres, a screen and a support are arranged under the separation bed, and an insulation layer or a circulating water jacket is arranged outside the cylinder; flow meters for checking and controlling the flow rate and concentration meters for detecting the concentration of the solution are appropriately arranged on the inlet and outlet interfaces and the outlet pipelines of the inlet and outlet interfaces of the chromatographic column; the required automatic valves and temperature measuring components are arranged on each interface and its connecting pipeline; the instrument and the automatic valve are connected to the intelligent controller, the intelligent controller is connected to the computer, and the control, segmentation logic and flow control of the inlet (boric acid-sodium hydroxide aqueous solution), water inlet, material discharge (aqueous solution containing a certain concentration of boric acid), and water outlet are realized through computer settings, thereby controlling the direction of the liquid outlet and segmenting and collecting the material outlet. The concentration meter includes a boric acid concentration transmitter and a conductivity transmitter.
[0021] In the separation by chromatography 10 B. 11 In process B, the boric acid and sodium hydroxide used to prepare the boric acid-sodium hydroxide aqueous solution should have appropriately high purity, and the impurity content other than water should preferably be less than 0.1wt%, and more preferably less than 0.03wt%; the water used to prepare the boric acid-sodium hydroxide aqueous solution and the pure water used as the desorption liquid should not contain organic components and O2, and the conductivity should be less than 0.2μs / cm. It is preferably high-purity distilled water obtained by further distillation after deionized pure water or reverse osmosis pure water is slightly boiled to remove impurities such as O2 and CO2.
[0022] When the adsorption and separation efficiency of the chromatographic column is found to be reduced, it can be regenerated with a 0.2-0.5 mol / L sodium hydroxide aqueous solution. After regeneration, the inlet water is rinsed until the conductivity of the discharged water is lower than 10 μs / cm, so that the performance of the chromatographic column can be restored to a large extent; the discharged sodium hydroxide aqueous solution contains sodium borate and can be used to prepare the boric acid-sodium hydroxide aqueous solution with a pH of 6-7.5.
[0023] The output of the chromatographic column (aqueous solution containing boric acid) and the water are separated and collected to obtain a certain concentration and 10 B. 11 The boric acid aqueous solution with B abundance can be further processed and utilized after preliminary concentration by reverse osmosis; the discharged water can be recycled as desorption liquid; the remaining liquid flow can be collected, concentrated by reverse osmosis and utilized as the ingredient of the boric acid-sodium hydroxide aqueous solution.
[0024] The beneficial effects of the present invention include: preparing a boron isotope separation resin microsphere, loading ferroferric oxide nanoparticles in the inner pores of the resin microsphere, which can be loaded into a chromatographic column, using boric acid-sodium hydroxide aqueous solution as a raw material and pure water as a desorption liquid,10 B. 11 The adsorption and separation of B and the chromatographic separation are simple and easy to operate. 10 B was enriched to a higher degree, and the boric acid adsorption capacity of the chromatographic column and 10 B. 11 The B separation performance can be basically restored through regeneration treatment with sodium hydroxide aqueous solution, thereby obtaining a longer service life. The overall performance is better than the existing technology and has certain application prospects.
[0025] From the effects of the following embodiments, comparative examples, and application test examples, it is believed that the main principles of the present invention are as follows, and the above beneficial effects are also the result of the combined effects of the following factors:
[0026] 1. In step (1) of the method for preparing boron isotope separation resin microspheres, the polystyrene-divinylbenzene resin microspheres are added with dimethyl sulfoxide and swelled at 50-65° C. for more than 3 hours. After being sulfonated with concentrated sulfuric acid until the sulfonation rate reaches 0.3-0.4 mmol / g, they have ion exchange capacity and good overall hydrophilicity. Concentrated sulfuric acid can be miscible with dimethyl sulfoxide, and sulfuric acid can quickly enter the inner pores of the resin microspheres, so that the sulfonation grafting reaction of the resin microspheres is more uniformly distributed among all the resin microspheres and in a single resin microsphere, and the sulfonation rate is easier to control to 0.3-0.4mmol / g; while in the conventional method of using conventional swelling agents such as dichloroethane to swell the resin and then perform sulfonation treatment, since the solubility of concentrated sulfuric acid in dichloroethane is very low and the two are easy to separate, the sulfonation rate is difficult to control to 0.3-0.4mmol / g, and the macroscopic distribution uniformity of the sulfonation grafting reaction between the resin microspheres and in a single resin microsphere is poor, which is not suitable for the present invention.
[0027] 2. In step (1), the sulfonation rate of the resin microspheres reaches 0.3-0.4mmol / g, that is, after the primary ion exchange transformation and water washing, the ammonium type macroporous polystyrene-divinylbenzene ion exchange resin microspheres obtained have a sulfonic acid group grafting amount much lower than the 4-5mmol / g of the conventional strong acid cation exchange resin, the purpose is to reduce the excessive occupation of the grafted sulfonic acid groups on the inner pore volume, so as to obtain a larger inner pore volume and specific surface area, improve the loading capacity and obtain better ferric oxide adsorption capacity and microsphere inner pore mass transfer capacity under the condition of equal ferric oxide loading amount. It is found that the size and number of ferric oxide grains can be affected and controlled to a certain extent. The reason should be that after the resin microspheres are converted to iron type by secondary ion exchange, the iron sulfonate on the inner pore surface plays the role of crystal seed; the lighter degree of sulfonation, that is, the hydrophilic modification of the polystyrene-divinylbenzene resin microspheres is achieved, which provides conditions for the subsequent immersion of ammonia solution and the spraying and inhalation of ferric chloride-ferrous chloride aqueous solution.
[0028] 3. In step (2), the ferric chloride-ferrous chloride aqueous solution sprayed by atomization has a high concentration and a certain viscosity. Even if it is completely absorbed into the resin microspheres, the distribution of ferric chloride and ferrous chloride components in the resin microspheres is still uneven. It is necessary to go through the 3-5h static homogenization process to achieve a basically uniform distribution in the resin microspheres. This is an important condition for the method of the present invention to load ferric oxide nanoparticles more evenly in the inner pores of the resin microspheres. During the homogenization and secondary ion exchange transformation treatment process, the ferric chloride-ferrous chloride aqueous solution absorbed into the resin microspheres is evenly distributed in the inner pores, including the homogenization of the solution distribution and the homogenization of the chemical composition. The secondary transformation is an ion exchange transformation from ammonium type to trivalent iron type. In the ferric chloride-ferrous chloride aqueous solution, when containing 0.01-0.03mol / L of titanium trichloride, the boric acid adsorption capacity and 10 B. 11 B separation effect, the reason may be that the hydrolysis product of titanium trichloride improves the surface properties of ferroferric oxide nanoparticles.
[0029] 4. In step (2), before the ammonia-nitrogen gas flow is introduced for treatment, 25-40% of the total weight of the water contained in the resin microspheres is removed by vacuum evaporation, so that the ferric chloride-ferrous chloride aqueous solution (containing more than 700g of water per liter of spraying liquid) in the inner pores is concentrated to form more ammonia mass transfer channels required for the ammonia-nitrogen gas flow treatment process in step (3), and the boron isotope separation resin microspheres finally prepared have better performance than when the vacuum evaporation for removing 25-40% of the total weight of the water contained in the resin microspheres is omitted. 10 B. 11 The main reason for the improved adsorption and separation performance of B boric acid is that the method of the present invention can obtain a relatively uniform distribution of ferroferric oxide nanoparticles in the inner pores of the resin microspheres. The boron isotope separation resin microspheres prepared by using the dried ammonium type resin microspheres, spraying ferric chloride-ferrous chloride aqueous solution, vacuum evaporation to remove part of the water, treating with the ammonia-nitrogen gas flow, and generating ferroferric oxide nanoparticles in the inner pores also have better adsorption and separation performance than the hydrogen type resin microspheres obtained by sulfonation and then washing in step (1), directly spraying ferric chloride-ferrous chloride aqueous solution, vacuum evaporation to remove part of the water, treating with the ammonia-nitrogen gas flow, and generating ferroferric oxide nanoparticles in the inner pores. 10 B. 11The main reason for the improved adsorption and separation performance of B boric acid may be that the method of the present invention can obtain a better distribution of ferroferric oxide nanoparticles in the inner pores of the resin microspheres, and the latter may also be more easily distributed in the inner surface layer and the inner pore openings of the resin microspheres. During the treatment process at a temperature of 50-60°C, a relative humidity of 30-40%, and a nitrogen gas flow containing 0.5-1v% ammonia, the precipitation reaction of ferric chloride-ferrous chloride proceeds slowly, so that the generated ferroferric oxide nanoparticles are more evenly deposited in the inner pores of the resin microspheres, and are less concentrated on the surface layer and the pore openings of the microspheres. The microsphere material prepared under other precipitation conditions is 10 B. 11 B separation effect has deteriorated; among them, the relative humidity of 30-40% of the ammonia nitrogen gas flow can ensure that the generation reaction of iron tetroxide nanoparticles is carried out in the liquid phase on the inner pore surface.
[0030] 5. In step (2), during the water washing process after the treatment with the ammonia-nitrogen gas flow, the drum drives the friction and flushing of the resin microsphere material, so that the surface of the resin microsphere is fully ground, and a small amount of ferroferric oxide nanoparticles deposited on the surface of the resin microsphere is basically ground and removed; thus, the prepared boron isotope separation resin microsphere is resistant to the boric acid-sodium hydroxide aqueous solution. 10 B. 11 The adsorption and separation effect of B should be mainly due to the effect of the ferroferric oxide nanoparticles in the inner pores. The effect of treating the resin microsphere material with the sodium hydroxide aqueous solution with a concentration of 0.8-1 mol / L and a temperature of 30-40°C (the liquid volume is 1-1.5 times the accumulated volume of the resin microsphere material) is to convert the sulfonic acid group grafted on the surface of the inner pores of the resin microspheres from ammonium type (pH weakly acidic) to sodium type (pH neutral, i.e., four-time ion exchange transformation), which to a certain extent provides a pH neutral solution condition for the ferroferric oxide nanoparticles, thereby to a certain extent improving the boron isotope separation resin microspheres prepared in the boric acid-sodium hydroxide aqueous solution. 10 B. 11 B adsorption, separation effect; when the sodium hydroxide aqueous solution treatment is not performed 10 B. 11 B boric acid adsorption, separation effect becomes worse. After the process of introducing the ammonia nitrogen gas stream to carry out the precipitation reaction of ferric chloride-ferrous chloride and generate ferroferric oxide nanoparticles is completed, the sulfonic acid group is converted from trivalent iron type to ammonium type (i.e., three ion exchange transformation). High-purity nitrogen is used to maintain the positive pressure in the drum, the O2 content of the ammonia nitrogen gas stream is lower than 30ppmv and deoxygenated water is used, the purpose is to avoid the oxidation of ferrous components and ensure the generation and surface state of ferroferric oxide nanoparticles.
[0031] 6. The present invention dynamically tests the boron isotope separation resin microspheres in boric acid-sodium hydroxide aqueous solution under chromatographic column conditions. 10 B. 11The adsorption and separation effect of B can be reflected in a large abundance range by one adsorption and separation operation and a few abundance measurements. 10 B. 11 The B separation effect is more practical than the static test method; it can also illustrate that the boron isotope separation resin microspheres prepared by the method of the present invention, and the ferroferric oxide nanoparticles loaded thereon, have an effect on the boric acid-sodium hydroxide aqueous solution with a pH of 6-7.5. 10 Component B has good affinity, and the pure water desorption method is simpler, the corrosion problem is lighter, the strength and wear resistance of the resin microspheres are significantly improved after the inner pores are loaded with ferroferric oxide, and the volume change rate during the operation of the chromatographic column is reduced with the concentration of the liquid flow. The impurity content other than water in the boric acid and sodium hydroxide used to prepare the boric acid-sodium hydroxide aqueous solution is less than 0.1wt%; the high-purity distilled water prepared by further distillation after the deionized pure water or reverse osmosis pure water is slightly boiled to remove impurities such as O2 and CO2 is used to prepare the boric acid-sodium hydroxide aqueous solution, and as a desorption liquid, the contamination of the impurity components contained in the boron isotope separation resin microspheres is reduced. Under the combined effect of these factors, the long-term adsorption separation performance and service life of the chromatographic column are guaranteed.
[0032] 7. Under chromatographic column conditions, in boric acid-sodium hydroxide aqueous solution 10 B. 11 In the separation process of B, high-purity distilled water was used as the desorption liquid, which can achieve a better separation effect. This shows that the adsorption amount of boric acid on the surface of the FeO nanoparticles loaded by the resin microspheres is roughly proportional to the boric acid concentration. 10 B. 11 The B separation coefficient is less affected by changes in boric acid concentration.
[0033] 8. After the adsorption and separation efficiency of the chromatographic column decreases, it can be regenerated and substantially restored to its performance by using a 0.2-0.5 mol / L sodium hydroxide solution. The reason may be that the surface of the ferroferric oxide nanoparticles supported by the resin microspheres gradually generates and deposits a polymer of boric acid, which is difficult to be washed out with water and affects the adsorption and separation performance of the chromatographic column. However, it can be dissolved and washed out by using a 0.2-0.5 mol / L sodium hydroxide aqueous solution, thereby substantially restoring the adsorption and separation performance of the chromatographic column. The discharged sodium hydroxide aqueous solution contains the depolymerization of the boric acid polymer to generate sodium borate, which can be used to prepare the boric acid-sodium hydroxide aqueous solution of pH 6-7.5. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is specifically described and illustrated below in conjunction with embodiments.
[0035] Example 1
[0036] The boron isotope separation resin microspheres of this embodiment were trial-produced together with the company's affiliated units. The preparation method includes the following steps:
[0037] (1) Take the cross-linking degree of 25 and the specific surface area of 152m 2 30 kg of polystyrene-divinylbenzene resin microspheres (white spheres obtained by removing the porogen from a mixed ingredient containing a porogen after being formed into spheres by suspension polymerization, washing with hot water and cold water in succession, and drying, with an outer diameter range of 0.6-0.9 mm and being hydrophobic) with a pore volume of 0.83 mL / g, an average pore diameter of 22 nm, and drying (120°C x 3h drying loss of 0.13 wt%) were placed in a glass-lined reactor (volume 300 L, no water in the reactor, and a discharge port and a liquid discharge port with a polytetrafluoroethylene filter membrane at the bottom of the reactor), the reactor was sealed, evacuated to below 3 kPa (absolute pressure), filled with high-purity nitrogen (99.99v%, O2 content less than 30ppmv) to 30-40 kPa (gauge pressure), and the process was repeated 3 times to replace the air in the reactor and maintain positive pressure in the following operations of this step , press in 135 kg of dimethyl sulfoxide (purity 99.7 wt%), raise the temperature to 60° C. and swell at 60-65° C. for 3 h, start stirring, press in 12 kg of 93 wt% concentrated sulfuric acid for sulfonation treatment, control the temperature at 60-65° C., react for 2.8 h, the sulfonation rate reaches 0.36 mmol / g (i.e., 0.36 meq / g, hydrophilic, the sampling amount is about 35 g based on the total amount of washed and dried sulfonated resin microspheres), stop stirring, discharge the liquid phase through the bottom discharge port of the kettle, inject water to wash until the pH value of the water outlet at the bottom discharge port of the kettle is 2.2, add 5 kg of 3.2 mol / L ammonia solution, stir well, and soak for 4 h, inject water to wash until the conductivity of the water outlet at the bottom discharge port of the kettle is lower than 100 μs / cm, and obtain water-containing ammonium-type macroporous polystyrene-divinylbenzene ion exchange resin microspheres;
[0038] During the sulfonation treatment, the weight ratio of polystyrene-divinylbenzene microspheres, dimethyl sulfoxide, and concentrated sulfuric acid is 1:4.5:0.4;
[0039] (2) The ammonium-type macroporous polystyrene-divinylbenzene ion exchange resin microspheres containing water in step (1) are transferred to a rotary drum (with a capacity of 300 L, a discharge port and a liquid discharge port with a polytetrafluoroethylene filter membrane, and the atomizing nozzle adopts a hydraulic atomization method when spraying liquid and water, and high-purity nitrogen and ammonia-containing nitrogen gas are also introduced by the atomizing nozzle), sealed and started to rotate, and vacuum dried at 60-70° C. for 8 h until the water content is 0. .7wt%, to obtain dried ammonium type resin microspheres (about 31.8kg, 30g sample was taken to measure the saturated water absorption volume of 0.80mL / g); further evacuated and cooled to 50-60°C, filled with high-purity nitrogen to positive pressure, and atomized sprayed with a ferric chloride-ferrous chloride aqueous solution with a concentration of 2.4mol / L and a temperature of 50-60°C (the concentrations of ferric chloride and ferrous chloride were 1.6mol / L and 0.8mol / L, respectively, and the metal impurity content was less than 35mg / L)
[0040] 20.3L, spraying time 5h, the drum continues to rotate for 0.5h until the surface solution of the resin microspheres is completely absorbed, then stops rotating, stands for 4h for homogenization (homogenization of the ferric chloride-ferrous chloride aqueous solution initially absorbed in the resin microspheres), and during the spraying and homogenization process, maintains the temperature of the resin microsphere material at 50-60°C and the positive pressure in the drum at 30-50kPa; the spraying volume of the ferric chloride-ferrous chloride aqueous solution is about 80% of the saturated water absorption volume of the dried ammonium type resin microspheres;
[0041] Start the drum, control the external heating temperature at 60-70°C and the required vacuum conditions, and evaporate and remove about 34% of the total weight of water contained in the resin microsphere material evenly within 10 hours (fix the external heating temperature and adjust the vacuum degree, condense the exhaust steam at 1-3°C through an electronic refrigerator, and control the condensed water amount to be basically uniform and uniform), fill with high-purity nitrogen through an atomizing nozzle to a positive pressure of 30kPa, and reduce the temperature of the resin microsphere material to 50-60°C; the drum continues to rotate, and introduces a temperature of 50-60°C, a relative humidity of 40-45%, and a content of 50-60°C at a required fixed flow rate. A nitrogen gas stream containing 0.8-1v% ammonia and an O2 content of less than 30ppmv is used to treat the resin microsphere material. After ventilating for 5.8h, no more ammonia is consumed (i.e., the ammonia content in the outlet and inlet gas streams is the same), and the ammonia-containing nitrogen gas stream is continued to be used for 0.5h; during the treatment with the ammonia-containing nitrogen gas stream, the temperature of the resin microsphere material is maintained at 50-60°C and the positive pressure in the drum is maintained at 30-50kPa; the ammonia-containing nitrogen gas stream is pressurized by an air pump and then recycled, and its relative humidity is cooled by an electronic refrigerator and condensed to remove part of the water vapor, and then ammonia is added and heated for use;
[0042] The drum continues to rotate and high-purity nitrogen is passed through to maintain the positive pressure in the drum. 135 kg of deoxygenated water (obtained by removing impurities such as O2 and CO2 from reverse osmosis pure water by micro-boiling) at 40-50°C is sprayed on the resin microsphere material (the amount of water sprayed is about 2.5 times the accumulated volume of the resin microsphere material). The drum is rotated for 45 minutes to wash the resin microsphere material once. The drum is stopped to drain the liquid between the resin microspheres. The washing and draining process is repeated 2-3 times. The drum is stopped to drain the liquid between the resin microspheres. The drum is started to spray the resin microsphere material with a concentration of 0.8 67.5 L of 35 mol / L sodium hydroxide aqueous solution at a temperature of 35°C (the spraying amount is about 1.25 times the accumulated volume of the resin microsphere material), stop the drum, let it stand for 2 hours and then drain the liquid between the resin microspheres; use room temperature deoxygenated water instead, repeat the water washing and draining process 4 times, the conductivity of the discharged water drops to 4.6 μs / cm, then spray room temperature deoxygenated water on the resin microsphere material again to immerse the resin microsphere material, discharge the resin microspheres and the immersion water into a container that has been replaced with nitrogen in advance and seal the container to obtain boron isotope separation resin microspheres.
[0043] As a result, the prepared water-containing boron isotope separation resin microspheres can be adsorbed by a magnet, have a smooth surface without sediment, and are black in appearance and cross section. Samples taken for detection contain 10.2wt% of Fe3O4 on a dry basis, and the net weight after deducting water is estimated to be about 35.1kg. This indicates that the generated ferroferric oxide nanoparticles are loaded in the inner pores of the resin microspheres; in step (2), during the water washing process after the treatment with the ammonia-nitrogen gas flow, when the drum drives the resin microsphere material to turn over, the surface of the resin microspheres is fully ground and rinsed, and a small amount of ferroferric oxide nanoparticles deposited on the surface of the resin microspheres are basically ground and removed.
[0044] Example 2
[0045] The boron isotope separation resin microspheres of this embodiment were prepared by using the trial production conditions described in Example 1 and basically following the steps (1)-(2) of Example 1, with the main difference being that in step (2), 20.3 L of a 3.0 mol / L ferric chloride-ferrous chloride aqueous solution (the concentrations of ferric chloride and ferrous chloride were 2.0 mol / L and 1.0 mol / L, respectively) was used instead.
[0046] As a result, the prepared boron isotope separation resin microspheres containing water can be adsorbed by a magnet, have a smooth surface without sediment, and are black in appearance and cross section. Samples taken for detection contain 12.4wt% of Fe3O4 on a dry basis, indicating that the generated ferroferric oxide nanoparticles are loaded in the inner pores of the resin microspheres; in step (2), during the water washing process after the treatment with the ammonia-nitrogen-containing gas flow, when the drum drives the resin microsphere material to turn over, the surface of the resin microspheres is fully ground and rinsed, and a small amount of ferroferric oxide nanoparticles deposited on the surface of the resin microspheres are basically ground and removed.
[0047] Example 3
[0048] Using the trial production conditions described in Example 1, the boron isotope separation resin microspheres of this example were prepared basically according to steps (1)-(2) of Example 1, with the main difference being that in step (2), the ferric chloride-ferrous chloride aqueous solution also contained 0.02 mol / L of titanium trichloride.
[0049] Comparative Example 1
[0050] Using the trial production conditions described in Example 1, all the operations of step (1) of Example 1 and part of the operations of step (2) were performed, with the main difference being:
[0051] In step (1), the amount of 93wt% concentrated sulfuric acid injected is 30kg, and the temperature is controlled at 80-85°C for sulfonation treatment. After the reaction time of 3.6h, the sulfonation rate reaches 4.15mmol / g; when the primary ion exchange transformation treatment from hydrogen type to ammonium type is carried out, 23kg of 8.8mol / L ammonia solution (temperature controlled below 75°C) is slowly added, stirred and soaked for 4h;
[0052] In step (2), the water-containing ammonium macroporous polystyrene-divinylbenzene ion exchange resin microspheres are dried in a rotary drum at 60-70° C. in vacuum for 11 h to a water content of 0.9 wt %, to obtain 58.0 kg of dried ammonium resin microspheres, and the saturated water absorption volume measured by sampling is 0.23 mL / g; it is believed that the dried ammonium resin microspheres have too small a pore volume and a poor effect of loading ferrosoferric oxide in the inner pores, and are not further prepared.
[0053] Comparative Example 2
[0054] Using the trial production conditions described in Example 1, the boron isotope separation resin microspheres of this comparative example were prepared in accordance with steps (1)-(2) of Example 1. The main difference is that in step (2), the operations of soaking in aqueous ammonia solution and then washing with water are omitted, and the hydrogen-type resin microsphere material is directly vacuum dried and all subsequent operations are completed, that is, the primary ion exchange transformation from the hydrogen type to the ammonium type is not performed.
[0055] The results showed that the prepared hydrated boron isotope separation resin microspheres could be adsorbed by a magnet, had a smooth surface without sediment, and were black in appearance and cross-section. Samples taken for testing contained 10.0 wt% Fe3O4 on a dry basis, indicating that the generated ferrosoferric oxide nanoparticles were loaded in the inner pores of the resin microspheres.
[0056] Comparative Example 3
[0057] Using the trial production conditions described in Example 1, the boron isotope separation resin microspheres of this comparative example were prepared basically according to steps (1)-(2) of Example 1, with the main difference being that in step (2), the ammonia content of the ammonia-nitrogen gas flow was increased from 0.8-1v% to 2-2.3v%, and no ammonia was consumed during ventilation for 3h.
[0058] The results showed that the prepared hydrated boron isotope separation resin microspheres could be adsorbed by a magnet, had a smooth surface without sediment, and were black in appearance and cross-section. Samples taken for testing contained 9.7wt% Fe3O4 on a dry basis, indicating that the generated ferrosoferric oxide nanoparticles were loaded in the inner pores of the resin microspheres.
[0059] Comparative Example 4
[0060] The boron isotope separation resin microspheres of this comparative example were prepared using the trial production conditions described in Example 1 and basically according to steps (1)-(2) of Example 1, with the main difference being that in step (2), the operation of spraying 0.8 mol / L sodium hydroxide aqueous solution onto the resin microsphere material was omitted, and then water was injected for washing until the conductivity of the discharged water dropped to 4.2 μs / cm, i.e., the fourth ion exchange transformation from ammonium type to sodium type was not performed.
[0061] The results showed that the prepared hydrated boron isotope separation resin microspheres could be adsorbed by a magnet, had a smooth surface without sediment, and were black in appearance and cross-section. Samples taken for testing contained 10.1 wt% Fe3O4 on a dry basis, indicating that the generated ferrosoferric oxide nanoparticles were loaded in the inner pores of the resin microspheres.
[0062] Comparative Example 5
[0063] Using some of the trial production conditions described in Example 1, the boron isotope separation resin microspheres of this comparative example were prepared according to the following steps:
[0064] In another glass-lined reactor (volume 600L, no water in the reactor), add the cross-linking degree 25 and specific surface area 152m 2 / g, pore volume 0.83mL / g, average pore diameter 22nm, dried (120℃x3h drying weight loss 0.13wt%) polystyrene-divinylbenzene resin microspheres (the same as used in Example 1, made from a mixed ingredient containing a porogen, after being spheroidized by suspension polymerization, the porogen is removed and the porogen is washed with hot water and cold water successively, and dried to obtain white balls, with an outer diameter range of 0.6-0.9mm, hydrophobic) 20kg, a closed reaction kettle, evacuated to below 3kPa (absolute pressure), and filled with high-purity nitrogen (99.99v%, O2 content less than 30ppmv) to 30-40kPa (gauge pressure) and repeat 3 times, replace the air in the kettle and maintain positive pressure in the following operations of this step, press in 90kg of dimethyl sulfoxide (purity 99.7wt%), raise the temperature to 60℃ and swell at 60-65℃ for 3h, start stirring, press in 20kg of 93wt% concentrated sulfuric acid, control the temperature at 80-85℃ for sulfonation treatment, and the sulfonation rate reaches 4.18mmol / g ( 4.18meq / g, hydrophilic), stop stirring, discharge the liquid phase through the bottom discharge port of the kettle, inject oxygen-free water to wash until the pH of the water outlet at the bottom discharge port is 2.4, add oxygen-free water to the volume of the feed liquid to about 550L; continue stirring, add 9.0L of 2.4mol / L ferric chloride aqueous solution, add 6.76L of 1.6mol / L ferrous chloride aqueous solution after 4h, raise the temperature of the feed liquid to 55℃ after 1h, control the temperature at 55-60℃ and add 8.8mol / L ammonia aqueous solution (dropping time 2.2h) to The pH value of the feed liquid is 8.1, and a coprecipitation reaction is carried out. After 1 hour, stirring is stopped, and the mixture is allowed to stand and age for 10 hours (the strength of the deposition layer on the surface of the resin microspheres gradually increases). Then, the liquid phase (black slurry, containing ferroferric oxide that has not been deposited on the surface of the resin microspheres and can be adsorbed by a magnet) is discharged through the discharge port at the bottom of the kettle, and oxygen-free water is added to wash until the pH value of the water discharged from the discharge port at the bottom of the kettle reaches 5.2. Oxygen-free water is added to immerse the resin microspheres, and the resin microspheres and the immersion water are discharged into a container that has been replaced with nitrogen in advance and the container is sealed to obtain resin microspheres for boron isotope separation.
[0065] As a result, the prepared aqueous boron isotope separation resin microspheres can be adsorbed by a magnet, with a slightly rough black deposition layer on the surface. The black surface deposition layer has a certain strength but will deform or even fall off when squeezed, and the cross section is light black. The sample was tested to contain 8.6wt% Fe3O4 on a dry basis. The preparation method of the boron isotope separation resin microspheres, the content and distribution of ferroferric oxide, are basically the same as those of Fe3O4@Resin-1 in the master's thesis "Preparation of ferroferric oxide-loaded resin and study of boron isotope separation performance" (Wang Qingfeng, Tianjin University, May 2021).
[0066] 200-220 mL of the boron isotope separation resin microspheres prepared in the above Examples 1-3 and Comparative Examples 2-5 were sampled respectively, and the surface moisture was removed by centrifugation and placed on a 350x250 mm stainless steel plate and spread into a thin layer. The samples were dried in a vacuum drying oven at 65-70°C for 5 h to constant weight, and the Fe3O4 content was detected by a chemical method. The XRD method was used to determine that the crystalline phase of iron in each boron isotope separation resin microsphere was Fe3O4, and the average grain size was 3.6 nm, 4.1 nm, 3.4 nm, 4.7 nm, 5.2 nm, 3.7 nm, and 12 nm, respectively.
[0067] Application Test Example 1
[0068] The boron isotope separation resin microspheres (soaked in water) prepared in the above Examples 1-3 and Comparative Examples 2-5 were respectively loaded into original straight cylindrical transparent organic glass (vertical) chromatographic columns with an inner diameter of 100 mm and a height of 5000 mm, and then subjected to boric acid-sodium hydroxide aqueous solution. 10 B and 11 Separation test of B.
[0069] The filling height of each resin microsphere is 4590mm (filling volume 36.0L, the bed is covered with five layers of Φ100mm, 60 mesh stainless steel screen, Φ3mm porcelain balls with a height of 120mm are filled on the screen, and the bed is supported by five layers of Φ100mm, 60 mesh stainless steel screen and Φ3mm porcelain balls to form a separation bed); the organic glass chromatographic column is assembled by a transparent organic glass inner tube (inner diameter 100mm) and a transparent organic glass outer tube, and circulating water can be passed through the outer tube for heat preservation or auxiliary temperature control; a high-purity nitrogen inlet / exhaust interface and a needle valve are arranged at the upper end of the chromatographic column, and a liquid inlet temperature controller is arranged and connected to control the boric acid-sodium hydroxide aqueous solution. The inlet temperature of the liquid and high-purity distilled water is controlled by the inlet automatic valve; the lower end of the chromatographic column is provided with and connected with a discharge temperature detector and a conductivity detector and a photoelectric detector for detecting the concentration of the solution; the inlet automatic valve, the inlet flow pump, the inlet temperature controller, the conductivity detector, the photoelectric detector and the discharge automatic valve are connected to an intelligent controller; the intelligent controller is connected to a computer, and the computer settings are used to realize the inlet selection, the flow rate of the inlet flow pump, the inlet temperature, the cutting and collection of the discharged liquid (cutting is performed according to the concentration of the discharged liquid). After the column is loaded, fill the entire chromatographic column with 25°C high-purity distilled water (made by further distilling deionized pure water after slight boiling to remove impurities such as O2 and CO2), and then wash the column for about 15 hours (first feed water at a flow rate of 18L / h for 1 hour, then reduce to 9L / h); at the same time, circulating water at 25°C is passed through the outer casing from bottom to top.
[0070] The dynamic separation test of each resin microsphere chromatographic column includes the following steps:
[0071] (a) First, 2.4 L of 25° C. boric acid-sodium hydroxide aqueous solution (6.67% of the volume of 36.0 L of the boron isotope separation resin microsphere bed in the chromatographic column) is added, and then high-purity distilled water at 25° C. is added, and the inlet flow rate is 2.0 L / h (the apparent or axial flow velocity in the separation bed is about 0.51 m / h, and the volume proportion of the resin microspheres in the separation bed is about 50%); the total concentration of boric acid and borate in the effluent is cut and collected according to the values before reaching the maximum value, after reaching the maximum value, 1-3 g / L, 3-5 g / L, and ≥5 g / L in terms of boric acid;
[0072] (b) When the total concentration of boric acid and borate in the effluent reaches a maximum value and starts to decrease, 2.4 L of 25° C. boric acid-sodium hydroxide aqueous solution and high-purity distilled water are introduced into the chromatographic column again, and the total concentration of boric acid and borate in the effluent continues to be cut and collected according to the values before reaching the maximum value, after reaching the maximum value, 1-3 g / L, 3-5 g / L, and ≥5 g / L in terms of boric acid;
[0073] (c) repeating steps (a) to (b);
[0074] The boric acid-sodium hydroxide aqueous solution was prepared from a saturated boric acid aqueous solution ( 10 B and 11 B abundance is 19.9% and 80.1% respectively), add 2mol / L sodium hydroxide aqueous solution, adjust to the required pH value, dilute to 2.4L with water and stir well to prepare, the boric acid and sodium hydroxide used in the preparation of the solution, the impurity content other than water is less than 0.03wt%, and the high-purity distilled water is used;
[0075] Among them, the separation resin microsphere chromatographic columns of Examples 1-3 were successively injected with boric acid-sodium hydroxide aqueous solutions with pH values of 7.0, 7.0, 7.0, 6.5, 6.0, 7.5, and 7.0, respectively, and the separation resin microsphere chromatographic columns of Comparative Examples 2-5 were successively injected with boric acid-sodium hydroxide aqueous solutions with pH values of 7.0, 7.0, 6.5, and 7.0, respectively.
[0076] A quasi-dynamic separation test was also carried out on the separation resin microsphere chromatographic columns of Examples 1-3 and Comparative Example 5. The boric acid-sodium hydroxide aqueous solution at 25° C. and pH 7.0 was introduced for 15 h (flow rate 2.0 L / h), and then high-purity nitrogen was introduced for 6 h (99.99 v%, flow rate 4.0 L / h) to discharge most of the solution between the resin microspheres, and then high-purity distilled water at 25° C. was introduced for 23 h (flow rate 2.0 L / h); the automatic discharge valve was closed when the high-purity distilled water was first introduced, and the automatic discharge valve was opened when the gas in the chromatographic column was exhausted (filled with liquid) and all the discharged liquid was collected, and each separation resin microsphere chromatographic column obtained an enrichment 10 B in aqueous boric acid solution.
[0077] The concentration of boric acid and borate in aqueous solution is determined by chemical method. 10 B. 11 The abundance of B was determined by ICP-MS.
[0078] The results of the dynamic separation test of each resin microsphere chromatographic column of Examples 1-3 and Comparative Examples 2-5 include: after the boric acid-sodium hydroxide aqueous solution of each pH value is introduced, the effluent collected by the chromatographic column of the separation resin microsphere of Examples 1-3, before the total concentration of boric acid and borate reaches the maximum value in terms of boric acid, the ≥3g / L portion 11 The abundance of B was more than 84.3%; after the total concentration of boric acid and borate reached the maximum value in terms of boric acid, the ≥3g / L part 10 The abundance of B was more than 26.1%, and the 1-3g / L part 10 B abundance is more than 29.4%; wherein, in Example 3 (in step (2) of the preparation process, the ferric chloride-ferrous chloride aqueous solution used also contains 0.02 mol / L titanium trichloride) boron isotope separation resin microsphere chromatographic column has the best boric acid adsorption capacity and 10 B. 11 B. Separation effect. In the chromatographic column for separating resin microspheres in Comparative Example 2-5, the collected effluent, before the total concentration of boric acid and borate reached the maximum value in terms of boric acid, was ≥3 g / L. 11 The abundance of B was lower than 83.5%. After the total concentration of boric acid and borate reached the maximum value in terms of boric acid, the ≥3g / L part 10 The abundance of B was lower than 23.6%, and the 1-3 g / L part 10 B abundance is lower than 25.6%, and the boric acid adsorption capacity and 10 B. 11 The separation effect of B is worse than that of the separation resin microsphere chromatographic column of Examples 1-3.
[0079] The quasi-dynamic separation test results of each resin microsphere chromatographic column of Examples 1-3 and Comparative Example 5 include: the chromatographic column of separating resin microspheres in Examples 1-3, the collected discharge liquid,10 The abundance of B was more than 24.3%, among which the separation resin microsphere chromatographic column of Example 3 had the best boric acid adsorption capacity and 10 B. 11 B separation effect; Comparative Example 5 separation resin microspheres chromatographic column, the collected discharge liquid 10 The abundance of B is 22.8%, and the boric acid adsorption capacity and 10 B. 11 The separation effect of B is also worse than that of the separation resin microsphere chromatographic column of Example 1-3.
[0080] It was found that the adsorption and separation efficiencies of the separation resin microsphere chromatographic columns of Examples 1-3 and Comparative Examples 2-5 were reduced after the above-mentioned dynamic separation test and quasi-dynamic separation test.
[0081] The separation resin microsphere chromatographic columns of Examples 1-3 were regenerated with a 25°C, 0.35 mol / L sodium hydroxide aqueous solution, respectively, with a liquid inlet time of 15 h (flow rate of 2.0 L / h), followed by a high-purity distilled water inlet for 20 h (flow rate of 2.0 L / h), rinsed until the conductivity of the effluent water was less than 10 μs / cm, and then 2.4 L of a 25°C boric acid-sodium hydroxide aqueous solution with pH values of 7.0, 7.0, 6.5, and 7.5 were successively inlet to carry out the dynamic separation test of the above steps (a)-(c), and the boric acid concentration and 10 B. 11 The results of B abundance detection show that the boric acid adsorption capacity and 10 B. 11 B separation effect is basically restored.
Claims
1. A method for preparing boron isotope separation resin microspheres, comprising the following steps: (1) Cross-linking degree 15-30, specific surface area 100-180m 2 / g, pore volume 0.6-1.0mL / g, dried polystyrene-divinylbenzene resin microspheres, add dimethyl sulfoxide in air-tight and water-free conditions, heat to 50-65°C for swelling for more than 3h, add 93-98wt% concentrated sulfuric acid for sulfonation treatment during stirring, control the temperature at 55-65°C, perform solid-liquid separation after the sulfonation rate reaches 0.3-0.4mmol / g, wash the microspheres with water until the pH value is ≥2, add 2-5mol / L ammonia solution to soak for 2-5h, and wash with water to obtain water-containing ammonium-type macroporous polystyrene-divinylbenzene ion exchange resin microspheres; During the sulfonation treatment, the weight ratio of polystyrene-divinylbenzene microspheres, dimethyl sulfoxide, and concentrated sulfuric acid is 1:(4-5):(0.3-0.5); (2) The ammonium macroporous polystyrene-divinylbenzene ion exchange resin microspheres containing water in step (1) are transferred to a rotary drum that can be evacuated, has external heating, and has an atomizing nozzle, and the rotary drum is sealed and started, and vacuum dried at 60-70° C. until the water content is less than 1wt%, thereby obtaining dried ammonium resin microspheres; further evacuating and cooling to 50-60° C., filling with high-purity nitrogen to positive pressure, and spraying an aqueous solution of ferric chloride-ferrous chloride with a concentration of 2-3 mol / L and a temperature of 50-60° C. for 4-6 hours, and the rotary drum is rotated for 0.5-1 hour until the surface solution of the resin microspheres is completely absorbed, and then the rotation is stopped, and the drum is allowed to stand for 3-5 hours for homogenization treatment; the spraying volume of the aqueous solution of ferric chloride-ferrous chloride is 70-85% of the saturated water absorption volume of the dried ammonium resin microspheres; in the aqueous solution of ferric chloride-ferrous chloride, the molar ratio of ferric chloride to ferrous chloride is 2:1; The drum is started, and the external heating temperature is controlled to be 60-70° C. and the required vacuum conditions are controlled. Within 8-12 hours, 25-40% of the total weight of the water contained in the resin microsphere material is uniformly evaporated and removed, and high-purity nitrogen is filled to a positive pressure, and the temperature of the resin microsphere material is reduced to 50-60° C.; the drum continues to rotate, and a nitrogen gas flow with a temperature of 50-60° C., a relative humidity of 35-45%, and 0.5-1v% ammonia is introduced at a required fixed flow rate to treat the resin microsphere material, so that no ammonia is consumed during ventilation for 4-8 hours, and the ammonia-containing nitrogen gas flow is continued for 0.5-1 hour; during the treatment with the ammonia-containing nitrogen gas flow, the temperature of the resin microsphere material is maintained at 50-60° C. and the positive pressure in the drum is maintained; The drum continues to rotate and high-purity nitrogen is passed to maintain the positive pressure in the drum. Deoxygenated water at 40-50° C. is sprayed on the resin microsphere material. The amount of water sprayed is 2-3 times the accumulated volume of the resin microsphere material. The drum is rotated for 30-60 minutes to wash the resin microsphere material once and grind the surface. The drum is stopped to discharge the liquid between the resin microspheres. The washing and drainage process is repeated 2-3 times. The drum is stopped to discharge the liquid between the resin microspheres. The drum is started to spray the resin microsphere material with a concentration of 0.8-1 mol / L, a sodium hydroxide aqueous solution at a temperature of 30-40°C, the liquid spraying amount is 1-1.5 times the accumulated volume of the resin microsphere material, the drum is stopped, and the liquid between the resin microspheres is discharged after standing for 2-3 hours; normal temperature deoxygenated water is used instead, and the water washing and liquid discharge process is repeated 3-5 times, and then the normal temperature deoxygenated water is sprayed on the resin microsphere material to immerse the resin microsphere material, and the resin microspheres and the immersion water are discharged into a container that has been replaced with high-purity nitrogen in advance and the container is sealed to obtain boron isotope separation resin microspheres.
2. The method for preparing boron isotope separation resin microspheres according to claim 1, characterized in that: In step (1), the polystyrene-divinylbenzene microspheres are white balls obtained by removing the porogen from a mixed ingredient containing a porogen through suspension polymerization, washing with water, and drying, and having an outer diameter of 0.6-0.9 mm.
3. The method for preparing boron isotope separation resin microspheres according to claim 1, characterized in that: In step (2), the drum is filled with nitrogen and maintained at a positive pressure of 15-30 kPa.
4. The method for preparing boron isotope separation resin microspheres according to claim 1, characterized in that: In step (2), the nitrogen gas flow has a temperature of 50-60°C, a relative humidity of 35-45%, contains 0.5-1v% ammonia, and has an O2 content of less than 30ppmv. The relative humidity is controlled by a condensation method or a desiccant method.
5. The method for preparing boron isotope separation resin microspheres according to claim 1, characterized in that: In step (2), the ferric chloride-ferrous chloride aqueous solution also contains 0.01-0.03 mol / L titanium trichloride.
6. The boron isotope separation resin microspheres as claimed in claim 1 are used for chromatographic separation of boric acid aqueous solution 10 B and 11 Application of B.
7. The boron isotope separation resin microspheres as claimed in claim 6 are used for chromatographic separation of boric acid aqueous solution 10 B and 11 The application of B is characterized in that The boric acid aqueous solution is a boric acid-sodium hydroxide aqueous solution with a pH of 6-7.5, and the desorption liquid is pure water.
8. The boron isotope separation resin microspheres as claimed in claim 7 are used for chromatographic separation of boric acid aqueous solution 10 B and 11 The application of B is characterized in that The separation operation conditions include: the column temperature of the chromatographic column is 15-35°C, the boric acid concentration in the boric acid-sodium hydroxide aqueous solution is 80-95% of the saturated concentration of boric acid in water under the column temperature condition, the apparent or axial flow rate of the boric acid-sodium hydroxide aqueous solution or pure water in the bed is 0.4-0.6m / h, and the liquid is fed in a top-in-bottom-out manner.
9. The boron isotope separation resin microspheres as claimed in claim 8 are used for the chromatography separation of boric acid aqueous solution 10 B and 11 The application of B is characterized in that The content of impurities other than water in the boric acid and sodium hydroxide used to prepare the boric acid-sodium hydroxide aqueous solution is less than 0.1wt%; the water used to prepare the boric acid-sodium hydroxide aqueous solution and the pure water used as the desorption liquid are high-purity distilled water obtained by further distilling deionized pure water or reverse osmosis pure water after slight boiling.
10. The boron isotope separation resin microspheres as claimed in claim 7 are used for the chromatography separation of boric acid aqueous solution 10 B and 11 The application of B is characterized in that When the adsorption and separation efficiency of the chromatographic column decreases, it is regenerated with a 0.2-0.5 mol / L sodium hydroxide aqueous solution.
Citation Information
Cited By
Process for preparing boron-10 acid by separating boron isotope
CN119461404A
A process for separating boron isotopes and preparing boric acid-10
CN119461404B
Separation method of boron isotope
CN120939751A